A Study on The Quadratic Jaco Graph - Jayasree, R.; Therese, A. Kulandai; Mary, U.; Kok, Johan (Communications in Mathematics and Applications, 2018)
In this paper we introduce the quadratic Jaco graph. The characteristics, properties and some graph invariants of quadratic Jaco graphs are also discussed. The observation that quadratic Jaco graphs are well-structured in respect of complete graphs and bridges led to the notion of braided complete graphs.